2017
DOI: 10.1136/thoraxjnl-2017-210431
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic phenotypes and their cardiovascular implications in obstructive sleep apnoea

Abstract: Among patients referred for OSA evaluation, routine polysomnographic data can identify physiological phenotypes that capture risk of adverse cardiovascular outcomes otherwise missed by conventional OSA severity classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
160
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(173 citation statements)
references
References 40 publications
7
160
0
Order By: Relevance
“…The longitudinal association between OSA clusters and continuous positive airway pressure (CPAP) adherence was first addressed by Gagnadoux et al 6 with reduced CPAP compliance in situations of an association between insomnia and OSA, or mild OSA and comorbid OSA. In the study of Zinchuck et al ,7 the percentage of patients with optimal CPAP adherence (>4 hours per night) varied broadly among clusters from 25% to 50%. The novelty here was to demonstrate in the whole study population that regular CPAP use was associated with a 36% decreased risk of primary outcome, but this attenuation varied by cluster.…”
mentioning
confidence: 97%
“…The longitudinal association between OSA clusters and continuous positive airway pressure (CPAP) adherence was first addressed by Gagnadoux et al 6 with reduced CPAP compliance in situations of an association between insomnia and OSA, or mild OSA and comorbid OSA. In the study of Zinchuck et al ,7 the percentage of patients with optimal CPAP adherence (>4 hours per night) varied broadly among clusters from 25% to 50%. The novelty here was to demonstrate in the whole study population that regular CPAP use was associated with a 36% decreased risk of primary outcome, but this attenuation varied by cluster.…”
mentioning
confidence: 97%
“…With respect to randomized grouping, the patients with more severe PLM index were statistically older in the studies by Koo et al [8], Chen et al [7], Zinchuk et al [32], and Xie et al [33]. In the studies by Lindner et al [9] and Xie et al [33], there were significantly more male patients in the groups with more severe PLM index than in those with a less severe PLM index.…”
Section: Discussionmentioning
confidence: 78%
“…The sensitivity test via one study removed revealed that the main results of the meta-analysis became statistically insignificant after removing the datasets by Koo et al [8], Zinchuk et al [32], and Xie et al [33]. This may have been due to the smaller sample sizes after removing these datasets.…”
Section: Sensitivity Testmentioning
confidence: 94%
See 1 more Smart Citation
“…Over the last several decades, we have witnessed substantial increases in the granularity of the morbid phenotype of OSA, and such observations have prompted us to rethink some of the stricter early concepts. Among them, rather than viewing OSA as a single disease model that is applicable to all patients, we have formulated the conceptual framework of distinct phenotypes of OSA that may be driven by different mechanisms, link to different clinical manifestations, and display divergent responses to therapy [1][2][3][4][5][6]. In this contextual setting, the aspirational goals of the field are to first and foremost identify those OSA patients likely to benefit from treatment and administer the correct intervention, i.e.…”
mentioning
confidence: 99%